Enhancing public health practice through a capacity-building educational programme: an evaluation - Negandhi, Preeti (Hum Resour Health, 2015)
BACKGROUND: The Post-Graduate Diploma in Public Health Management, launched by the Govt. of India under the aegis of the National Rural Health Mission in 2008, aims to enhance the managerial capabilities of public health professionals to improve the public health system. The Govt. of India invested enormous resources into this programme and requested an evaluation to understand the current processes, assess the graduates’ work performance and identify areas for improvement. METHODS: Quantitative telephone surveys as well as qualitative in-depth interviews were used. Graduates from the first three batches, their supervisors, peers and subordinates and faculty members were interviewed. Quantitative data were analysed using proportions, means and interpretative descriptions. Qualitative analyses involved transcription, translation, sorting, coding and filing into domains. RESULTS: Of the 363 graduates whose contact details were available, 138 could not be contacted. Two hundred twenty-three (223) graduates (61.43% of eligible participants) were interviewed by telephone; 52 in-depth interviews were conducted. Of the graduates who joined, 63.8% graduates were motivated to join the programme for career advancement and gaining public health knowledge. The content was theoretically good, informative and well-designed. Graduates expressed need for more practical and group work. After graduating, they reported being equipped with some new skills to implement programmes effectively. They reported that attitudes and healthcare delivery practices had improved; they had better self-esteem, increased confidence, better communication skills and implementation capacity. While they were able to apply some skills, they encountered some barriers, such as governance, placements, lack of support from the system and community, inadequate implementation authority and lack of planning by the state government. Incentives (both monetary and non-monetary) played a major role in motivating them to deliver public health services. They suggested that states should nominate candidates expected to make a significant contribution to the health system, recognition from a relevant authoritative national body and need for a placement cell, especially for the self-sponsored candidates. CONCLUSIONS: A continuous mechanism for interaction and dialogue with the graduates during and after completion of the programme should be designed. This evaluation helped by providing inputs for refining the programme.